Diane E. Griffin, physician–scientist extraordinaire - Arturo Casadevall; J. Marie Hardwick (Proceedings of the National Academy of Sciences, 2025)
In October 2024, the scientific world lost Diane E. Griffin, a highly accomplished physician–scientist who greatly heightened our understanding of viral pathogenesis. Apart from being a leading virologist in her time, she was unusual in working tirelessly to maintain the fabric of science through her service to journals, scientific societies, and the academies. She leaves a rich scientific legacy in explaining many facets of the pathogenesis of neurotropic viruses, including measles, and in a large network of trainees and colleagues who benefitted from her wisdom and care. In remembering Diane, we celebrate a great life in science and note with admiration how she leaves us with a shining example to emulate.